Aires protégées et écotourisme de vision de la grande faune : développement d’une approche méthodologique pour évaluer les circuits et application au complexe Oti-Kéran-Mandouri au Togo (Afrique de l’Ouest) - Dabitora Koumantiga; Kpérkouma Wala; Madjouma Kanda; Marra Dourma; Koffi Akpagana (Études Caribéennes)
Vision tourism in protected areas is one of the activities of valorization and management of these ecosystems. However, wildlife observation tourism can contribute to tarnishing the image of the protected area to the extent that the circuits offered to customers do not meet its expectations. Thus, scientific tools to obtain reliable information on tourist circuits of a protected area can contribute to the reliable planning of ecotourism activities in these protected ecosystems. For this purpose, this paper presents a methodological approach for assessing the capacity of ecotourism circuits in a protected area, to meet the expectations of ecotourists in relation to the observations of large and medium wild mammals found there. In this approach, the essential parameters to be considered in the evaluation of the circuits were presented. They are mainly the probability of observation, the diversity of observation and the recurrence of observation. The application of this methodological approach in the Oti-Kéran-Mandouri (OKM) complex, has shown that the present state of this complex is poorly adapted for the promotion of vision tourism of large and medium mammals.